Unoccupied electronic structure of TiOCl studied by x-ray absorption near-edge spectroscopy - Glawion, Sebastian; Haverkort, Maurits W. (Arxiv, 2011)
We study the unoccupied electronic structure of the spin-1/2 quantum magnet TiOCl by x-ray absorption near-edge spectroscopy (XANES) at the Ti L and O K edges. Data is acquired both in total electron and fluorescence yield mode (TEY and FY, respectively). While only the latter allows to access the unconventional low-temperature spin-Peierls (SP) phase of TiOCl the signal is found to suffer from significant self-absorption in this case. Nevertheless, we conclude from FY data that effects of the SP distortion on the electronic structure are absent within experimental accuracy. The similarity of room-temperature FY and TEY data, the latter not being obscured by self-absorption, allows us to use TEY spectra for comparison with simulations. These are performed by cluster calculations in D$_{4h}$ and D$_{2h}$ symmetries using two different codes. We extract values of the crystal-field splitting (CFS) and parametrize our results in often found notations by Slater, Racah and Butler. In all cases, good agreement with published values from other studies is found.